2013
DOI: 10.2319/051313-371.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing the severity of buccal caries lesions in governmental and private orthodontic patients at debonding, using the ICDAS-II and the DIAGNOdent Pen

Abstract: Objectives: To clinically evaluate the prevalence of buccal caries and white spot lesions (WSLs) at debonding in governmental and private orthodontic patients, using the International Caries Detection and Assessment System (ICDAS-II) and the DIAGNOdent Pen, and to study the correlation between the two methods. Materials and Methods: A cross-sectional study was carried out on the nonextracted premolars and anterior teeth of 89 orthodontic patients. They were recruited into two groups based on the treatment cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
0
16
0
6
Order By: Relevance
“…8 Dental caries occurs as a result of the metabolism of bacteria lodging in plaque attached to the tooth, and hence toothpaste and tooth brushing should help reduce the adherence of these microorganisms within the plaque biofilm in the mouth. This is supported by some clinical studies 9,10 which have shown that regular tooth brushing with well-formulated fluoride toothpaste can reduce the incidence of dental caries. Significantly, the dental health organisation in Nigeria has advocated preventive and prophylactic measures in the management of dental caries through regular hygiene and dietary modifications.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…8 Dental caries occurs as a result of the metabolism of bacteria lodging in plaque attached to the tooth, and hence toothpaste and tooth brushing should help reduce the adherence of these microorganisms within the plaque biofilm in the mouth. This is supported by some clinical studies 9,10 which have shown that regular tooth brushing with well-formulated fluoride toothpaste can reduce the incidence of dental caries. Significantly, the dental health organisation in Nigeria has advocated preventive and prophylactic measures in the management of dental caries through regular hygiene and dietary modifications.…”
Section: Introductionmentioning
confidence: 67%
“…Published literature suggests that brushing regularly with well formulated fluoride toothpastes can prevent the onset of this disease. 9,10,26,27 In the present in vitro study, eggshell powder was used as a substitute for human tooth material to verify the effectiveness of five commercially available toothpastes in the prevention of dental caries. SEM and EDX were used to study the surface morphology and the calcium and phosphate composition of the brands of toothpastes before and after agitation with eggshell powder.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the validity of diagnosing the severity of buccal caries lesions using digital photographs, the clinical examination was considered as the gold standard. In a previous evaluation, the first author (N.A) showed excellent intra-examiner and inter-examiner reliability with another co-author in the clinical examination using the ICDAS-II criteria, with kappa values of 0.88 and 0.87, respectively [17].…”
mentioning
confidence: 98%
“…18 Klinik bir çalışmanın sonucunda; beyaz nokta lezyonlarında DIAGNOdent Pen'in güvenilir ve ICDAS kriterleri ile uyumlu olduğu bulunmuştur. 20 DİAGNOdent Pen ile Caries ID yi karşılaştıran bir çalışmada; Caries ID nin çürük saptamada daha başarılı olduğu ancak çürük olmadığı durumda DİAGNOdent e göre daha fazla yanlış pozitif cevap verdiği bulunmuştur. 21…”
Section: Görsel Ve Radyografik Değerlendirmeunclassified